Design of Normal Concrete Mixtures Using Workability-Dispersion-Cohesion Method - Hisham Qasrawi (Advances in Civil Engineering)
The workability-dispersion-cohesion method is a new proposed method for the design of normal concrete mixes. The method uses special coefficients called workability-dispersion and workability-cohesion factors. These coefficients relate workability to mobility and stability of the concrete mix. The coefficients are obtained from special charts depending on mix requirements and aggregate properties. The method is practical because it covers various types of aggregates that may not be within standard specifications, different water to cement ratios, and various degrees of workability. Simple linear relationships were developed for variables encountered in the mix design and were presented in graphical forms. The method can be used in countries where the grading or fineness of the available materials is different from the common international specifications (such as ASTM or BS). Results were compared to the ACI and British methods of mix design. The method can be extended to cover all types of concrete.